Orbits of invariant subspaces of algebraic linear operators - Benabdallah, Khalid; Charles, Bernard (Linear algebra and its applications, 1995)
Let E be a vector space over a field K, and A an algebraic K-linear operator on E. We describe the orbits under the action of the commutant of A and of the group of the invertible elements of the commutant of A on the lattice of A-invariant subspaces.